GAMBARAN KEPUASAN PELAYANAN PERAWATAN GIGI TIRUAN LEPASAN BERBASIS AKRILIK PADA MASYARAKAT KELURAHAN MOLAS - Chuanda, Chandra (e-GiGi, 2014)
Abstract: Oral health is very important in our daily life activities such as eating, drinking, and talking, as well as socialization and self-confidence. Individuals with oral health problems including tooth loss and using removable denture which does not function properly usually have many complaints. From the standpoint of patients, denture care services are successful if the patients are satisfied with the services provided, willing, and feeling comfortably to use dentures. This study aimed to describe the satisfaction of acrylic based removable denture care services in Molas. This was a descriptive study by using questionnaires. Samples were 66 people. Satisfaction is the difference between the expectation and experience of people at the removable denture care services and is measured based on five dimensions of satisfaction as follows, reliability, responsiveness, assurance, empathy, and tangibles. Data were analyzed by using the Excel program and then presented in tabular forms of Service-Quality and Cartesian diagram. The results showed the average scores of the dimensions as follows: reliability -0.6, responsiveness -0.5, assurance -0.7, empathy -0.42, and tangibles -0.6. Assurance was the most complained dimension. Conclusion: The difference between the level of expectation and the experience of patients were unsatisfactory or still below expectation. Keywords: satisfaction service, denture care, removable denture based acrylik.Â Â  Abstrak: Kesehatan gigi dan mulut yang baik dibutuhkan dalam berbagai aspek kehidupan sehari-hari seperti makan, minum, bicara, sosialisasi, dan rasa percaya diri. Individu dengan gangguan kesehatan gigi dan mulut termasuk yang mengalami kehilangan gigi dan menggunakan gigi tiruan namun tidak berfungsi maksimal umumnya mempunyai banyak keluhan. Dari sudut pandang pasien, pelayanan perawatan gigi tiruan dikatakan berhasil bila pasien puas terhadap pelayanan yang diberikan, mau, dan nyaman menggunakan gigi tiruan. Penelitian ini bertujuan untuk mengetahui gambaran kepuasan pelayanan perawatan gigi tiruan lepasan berbasis akrilik pada masyarakat Molas. Penelitian ini bersifat deskriptif dengan menggunakan kuesioner. Sampel berjumlah 66 orang. Gambaran selisih antara harapan dan pengalaman masyarakat pada pelayanan perawatan gigi tiruan lepasan diukur berdasarkan 5 dimensi kepuasan yaitu, reliability, responsiveness, assurance, emphaty, dan tangibles. Analisis data menggunakan program Excel dan kemudian disajikan dalam bentuk tabel Service-Quality dan Diagram kartesius. Hasil penelitian memperlihatkan skor rata-rata dimensi reliability -0,6, responsiveness -0,5, assurance -0,7, emphaty -0,42, dan tangibles -0,6. Assurance merupakan dimensi yang paling banyak dikeluhkan. Simpulan: Selisih antara tingkat harapan dengan pengalaman pasien semuanya tidak memuaskan pasien atau masih di bawah harapan pasien. Kata kunci: kepuasan pelayanan, perawatan gigi tiruan, gigi tiruan bebasis akrilik